2021
DOI: 10.3390/agronomy11050849
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming with Potassium Nitrate and Gibberellic Acid Enhances the Performance of Dry Direct Seeded Rice (Oryza sativa L.) in North-Western India

Abstract: Poor early growth and uneven crop establishment are reported as the major bottlenecks in wide-scale adoption and optimal yield realization of dry direct-seeded rice (DSR). Seed priming can potentially help overcome these problems in DSR. Therefore, laboratory and field studies were conducted at Punjab Agricultural University, Ludhiana, India, during kharif/wet-season 2018 and 2019 to evaluate the effect of different priming techniques on germination, establishment, growth, and grain yield of rice under DSR con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
4
12
0
Order By: Relevance
“…Dry DSR could be more advantageous over the other two methods 8 , 9 due to less time required for sowing, thus economizing time and labour, and saving water. Though PTR is the main rice transplanting system in Asia including India, DSR has now been gaining popularity 10 – 13 . For example, in China, DSR now covers 28% of the total rice area 14 , while in Sri Lanka and Malaysia, areas under DSR are > 93% (1.03 M ha) and 95% (0.67 M ha) respectively of their respective total rice area 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Dry DSR could be more advantageous over the other two methods 8 , 9 due to less time required for sowing, thus economizing time and labour, and saving water. Though PTR is the main rice transplanting system in Asia including India, DSR has now been gaining popularity 10 – 13 . For example, in China, DSR now covers 28% of the total rice area 14 , while in Sri Lanka and Malaysia, areas under DSR are > 93% (1.03 M ha) and 95% (0.67 M ha) respectively of their respective total rice area 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ali et al (2021) reported that there was a significant increase in final emergence (%), mean emergence time, and physiological attributes were observed in tomato while primed with 0.75% KNO 3 . Moreover, Dhillon et al (2021) noted that halo-priming with 2.0% KNO 3 in dry direct seeded rice were attributed to higher and rapid germination/crop emergence, better root growth, and improvement in yield parameters. In the present study it has also been realized that no rooting was observed except radicle in the non primed seedlings during study periods whereas, the seedlings from primed seeds generate more number of roots from the crown region.…”
Section: Resultsmentioning
confidence: 99%
“…Priming also minimizes effect of en-vironmental stress during the time of germination and ultimately leads to higher seedling emergence and stand establishment with vigorous growth (Marthandan et al, 2020;Ali et al, 2021). Such kind of pre-metabolic biological activities of priming are helpful for farmers because it reduces the time of emergence, cost of repeated seeding, fertilization and additional irrigation on treatment with various chemicals or bio-chemicals in different field crops and horticultural crops (Hussain et al, 2015;Ruttanaruangboworn et al, 2017;Ali et al, 2020;Acharya et al, 2020;Dhillon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional rice cultivation in the RWCS is characterized by intensive puddling followed by transplanting of 25- to 30-day-old seedlings, maintaining standing water in paddy fields for 2 weeks, and thereafter re-applying irrigation 2 days after the ponded water has disappeared due to infiltration into the soil ( Anonymous, 2020 ; Dhillon et al, 2021 ). This practice offers some benefits, such as competitive advantages against weeds and poor oxygen diffusion that restricts the germination of weeds, assured anaerobic conditions with a neutral soil reaction, and greater availability of nutrients, such as iron ( Bhatt and Kukal, 2015 ).…”
Section: Traditional Production Practices and Challengesmentioning
confidence: 99%
“…The continuous use of a single herbicide in rice for the control of Echinochloa spp. resulted in the emergence of new hardy weeds like Leptochloa chinensis (L.) Nees, Cynodon dactylon (L.) Pers., Ischaemum rugosum Salisb., Paspalum distichum L., Ludwigia hyssopifolia (G. Don) Exell, Eclipta prostrata L., Cyperus rotundus L., Cyperus iria L., Cyperus difformis L., and Fimbristylis miliacea (L.) Vahl ( Mahajan et al, 2012 ; Shekhawat et al, 2020 ; Dhillon et al, 2021 ). Due to the monocropping of the RWCS, the infestation of Phalaris minor Retz.…”
Section: Traditional Production Practices and Challengesmentioning
confidence: 99%